The Powerlessness of Cameroon’s Reunification Monuments - NFI, Joseph Lon (EAST WEST JOURNAL OF HUMANITIES, 2013)
This study attempts to investigate the symbolism and popularity of the Reuniﬁcation Monuments constructed in Yaounde and Mamfe some years after the political reuniﬁcation of the two Cameroons. These monuments were constructed to commemorate the reuniﬁcation of Cameroon, considered by many as the most signiﬁcant event in postcolonial Cameroon history. This study intends to investigate why the monuments became victims of neglect, indifference and even scorn from Cameroonians only a few decades after reuniﬁcation. An analysis of the data collected from interviews and secondary sources reveals that the monuments remain unpopular like the reuniﬁcation history itself largely due to the failure of the powers that be to project this aspect of Cameroon history. The monuments have, therefore, remained powerless, as they have not immortalized the reuniﬁcation of Cameroon, as is the case with reuniﬁcation monuments elsewhere.